2006
DOI: 10.1088/0954-3899/32/12/s24
|View full text |Cite
|
Sign up to set email alerts
|

Event-by-event fluctuations and the QGP phase transition

Abstract: Abstract. Fluctuations of thermodynamic quantities are fundamental to the study of QGP phase transition. Event-by-event fluctuations of many quantities have been studied by dedicated heavy-ion experiments. A brief review of recent experimental results is presented. The prospect for future study of fluctuations is discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Fluctuations of thermodynamic quantities such as temperature and entropy have been proposed to give evidence for the existence of QGP phase transition and also provide direct insight into the properties of the system created in heavy-ion collisions [ 15,22]. Active study of event-by-event fluctuations in heavy-ion collisions was initiated by experiments at the SPS and now very much applied to the data at RHIC energies.…”
Section: Event-by-event Physicsmentioning
confidence: 99%
“…Fluctuations of thermodynamic quantities such as temperature and entropy have been proposed to give evidence for the existence of QGP phase transition and also provide direct insight into the properties of the system created in heavy-ion collisions [ 15,22]. Active study of event-by-event fluctuations in heavy-ion collisions was initiated by experiments at the SPS and now very much applied to the data at RHIC energies.…”
Section: Event-by-event Physicsmentioning
confidence: 99%
“…With the production of large number of particles in each of the collisions, it has become possible to extract thermodynamic quantities on an event-by-event basis, rather than averaging over a sample of events. Event-by-event fluctuations of ǫ, T , mean transverse momentum, particle multiplicity, particle ratios, etc., as well as fluctuations of conserved quantities within finite detector acceptances have been proposed to provide dynamical information regarding the evolving system [2,3,4,5,6,7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The study of fluctuations and correlations has been suggested as a useful means to reveal the mechanism of particle production and the formation of Quark-Gluon-Plasma (QGP) in the relativistic heavy-ion collisions [1,2]. Correlations and fluctuations of the thermodynamic quantities and/or the produced particle distributions could be significantly altered when the system undergoes phase transition because the degrees of freedom is largely different between the hadronic matter and the quark-gluon matter.…”
Section: Introductionmentioning
confidence: 99%